Measuring "small-world" connectivity in international trade: a shift-share and ANOVA approach - Laurie Schintler; Rajendra Kulkarni; Roger Stough (European Regional Science Association (ERSA), 2002)
Improvements in telecommunications and transportation appear to be bringing the world closer making physical location less of a factor in determining interaction between nations. The formation of regional and global trading pacts and arrangements seem to be further contribution to this interaction. Some would argue that what is evolving, as a result of these developments, is a 'small world' network. This type of network has a high degree of cliquishness, or local connectivity, and a relatively short average minimum path, or strong overall network connectivity. 'Small-world networks' is a new concept that is receiving a lot of attention. Introduced by Watts and Strogatz (1998), a 'small-world network' is based on 'six degrees of separation' or the notion that everyone in the world is related to everyone else through at most six acquaintances. 'Six degrees of separation' arises from the existence of cliques and a few popular individuals who provide connections between these cliques. The huge appeal of 'small-world networks' lies in the impact they are said to have on dynamical systems. According to Watts and Strogatz(1998), for example, models of dynamical systems with small-world coupling display enhanced signal propagation speed, computational power, and synchronizability. Furthermore, contagious diseases tend to spread more freely in 'small-world networks'. These findings have profound implications for many manmade and natural systems. In a trading network, 'small-world' topology might contribute to the regional and global economic spillover effects. This paper introduces a method, based on shift-share analysis and one-way analysis of variance (ANOVA), which can be used to measure the extent of 'small-world' connectivity is evolving in a network. The shift-share model is basically a rule of thumb/empirical method and is used in identifying the "small world" activity. ANOVA is used as a theoretical explanation of the shift-share results and an alternate way to measure "small world". The model is applied to two distinct time periods, the first from 1996 to 1998 and the second from 1989 to 1992. The first time period is representative of the trading network topology that was present in the 1980's, in particular a lot of local trading arrangements (cliques) and very few multilateral alliances and agreements between nations of different cliques, while the latter time period reflects stronger local trading arrangements (cliques) and the introduction of multilateral and bilateral agreements between nations of different cliques. Results are summarized using a geographic information system.
Keywords: 330